Czy „pośród szczęku broni milczą muzy"? Poezja rosyjska po 24 lutego 2022 roku (wybrane przykłady internetowego projektu „No war – поэты против войны") - Wawrzyniec Popiel-Machnicki (Studia Rossica Posnaniensia, 2025)
"Amidst the clatter of arms, the muses are silent" the Latin maxim "Inter arma silent Musae" is based on a quote from Marcus Tullius Cicero's defence of Milo: "When arms rattle, laws are silent". The meaning of this expression, highly relevant today, is that art takes a back seat during an ongoing war. The invasion of Ukraine by the Russian Federation, started on February 24, 2022, which escalates the armed conflict that has been ongoing since 2014, serves as a pretext to verify whether Cicero's paraphrased statement holds true in the face of the battles between our eastern neighbours. This text is an attempt to analyse selected recent works within Russian poetry, created since the start of Russia's so-called "special military operation" and published online as a part of the international project "No war поэты против войны" initiated and realized by New York's KRIK Publishing House. In the context of scant studies on this topic, the conducted research constitutes a literary criticism novelty, demonstrating how Russian poets have responded to recent history, set against the backdrop of the Russo-Ukrainian war. The main thesis of the article emphasizes that in their poems, they clearly identify the Russian Federation as the main culprit in this conflict.